Multi-factor Authentication and their Approaches - Singh, Saroj (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
Multi-factor authentication is an approach to authentication which requires the presentation of two or more of the three authentication factors: a knowledge factor ("something the user knows"), a possession factor ("something the user has"), and an inherence factor ("something the user is")...